Detector corrections for particle identification in SAMURAI spectrometer - N. , D. Ton; B. , D. Linh; Seastar3 , collaborator (Nuclear Science and Technology, 2026)
: Superconducting Analyzer for MUlti particles from Radio Isotope beams (SAMURAI) is an advanced spectrometer at RIKEN for experiments in which complete kinematic is determined to derive invariant-mass spectroscopy and parallel momentum distribution. This report represents the basic structure and technical advantages of SAMURAI, which was utilized in the third campaign of the “Shell Evolution An Search for Two-plus energies At RIBF” (SEASTAR3) project. In adition, corrections for particle identification at the SAMURAI will be discussed. These corrections are a typical and crucial step in the data analysis process in SEATAR3 experiments. The particle identification results will be used for further analysis of the properties of nuclear structure of neutron-rich nuclei around N = 32, 34.